A deep learning aided bone marrow segmentation of quantitative fat MRI for myelofibrosis patients - Tariq, Humera; Hadjiiski, Lubomir; Malyarenko, Dariya; Talpaz, Moshe; Pettit, Kristen; Luker, Gary D.; Ross, Brian D.; Chenevert, Thomas L. (Frontiers in Oncology, 2025)
PurposeTo automate bone marrow segmentation within pelvic bones in quantitative fat MRI of myelofibrosis (MF) patients using deep-learning (DL) U-Net models.MethodsAutomated segmentation of bone marrow (BM) was evaluated for four U-Net models: 2D U-Net, 2D attention U-Net (2D A-U-Net), 3D U-Net and 3D attention U-Net (3D A-U-Net). An experienced annotator performed the delineation on in-phase (IP) pelvic MRI slices to mark the boundaries of BM regions within two pelvic bones: proximal femur and posterior ilium. The dataset comprising volumetric images of 58 MF patients was split into 32 training, 6 validation and 20 test sub-sets. Model performance was assessed using conventional metrics: average Jaccard Index (AJI), average Volume Error (AVE), average Hausdorff Distance (AHD), and average Volume Intersection Ratio (VIR). Iterative model optimization was performed based on maximizing validation sub-set AJI. Wilcoxon’s rank sum test with Bonferroni corrected significance threshold of p<0.003 was used to compare DL segmentation models for test sub-set.Results2D segmentation models performed best for iliac BM with achieved scores of 95-96% for the VIR and 87-88% for AJI agreement with expert annotations on the test set. Similar performance was observed for femoral BM segmentation with slightly better VIR but worse AJI agreement for U-Net (94% and 86%) versus A-U-Net (92% and 87%). 2D models also exhibited lower AVE variability (8-9%) and ilium AHD (16 mm). The 3D segmentation models have shown marginally higher errors (AHD of 19-20 mm for ilium and 10-12% AVE-SD for both bones) and generally lower agreement scores (VIR of 91-93% for ilium and 89-91% for femur with 85-86% AJI).Pairwise comparison across four U-Nets for three metrics (AHD, AJI, AVE) showed that AJI and AHD performance was not significantly different for 3D U-Net versus 3D A-U-Net and for 2D U-Net versus 2D A-U-Net. Except for AVE, for majority of performance metric comparisons 2D versus 3D model differences were significant in both bones (p<0.001).ConclusionAll four tested U-Net models effectively automated BM segmentation in pelvic MRI of MF patients. The 2D A-U-Net was found best overall for BM segmentation in both femur and ilium.